A Pilot Study of an AI Chatbot for the Screening of Substance Use Disorder in a Healthcare Setting - Tara Wright; Adam Salyers; Kevin Howell; Jessica Harrison; Joshva Silvasstar; Sheana Bull (AI)
Background: Screening for substance use disorder (SUD) is a critical step to address the ongoing opioid crisis in the U.S., but fewer than 10% of people at risk screen. Technology may play a role in substantially increasing screening by making screening accessible through artificially intelligent (AI) chatbots. Methods: This was a single-arm mixed-methods pilot study to establish the system usability of an AI chatbot delivering information about substances, substance use disorder, and treatment options, and implementing self-screening for anxiety, depression, and substance use disorder. Participants were asked to engage with the AI chatbot for seven days and could self-select to screen. Results: Of the 92 participants enrolled, 91 engaged with the system at least once, and 29 (32%) completed at least one screener. Those who screened were given a referral if they exhibited moderate or severe anxiety, depression, and/or SUD. Over three-quarters (83%) of those screened received a referral for treatment, and 50% of those referred made an appointment for care. Users indicated that they found the system helpful and informative, and they felt comfortable screening. Conclusions: While other AI systems that share information about mental health and substance use exist, we know of no other AI chatbot that is being deployed specifically to facilitate SUD screening and referral. The system we describe here shows potential to support self-screening. Users generally find the system acceptable to use. AI technology may allow for improved access to SUD screening and treatment referrals, a critical step in responding to the opioid crisis.